GESKIEDENIS EN ARGEOLOGIE (Historia, 2021)
Archaeological evz.dence, as a record of human activz.ty, isfully as important as conventional hzstory and should, therefore, be accorded a similar stt:ztus. Indeed, archaeological researches are that much more importantz a country like South Africa where the overwhelmzng part of the story of even relau.vely recent human activz"ty lies in the prehzstoric past.
Keywords: Interdisciplinary relationships; Methodological differences; Archaeological resources; Archaeology; Historical resources; Cultural history